Menstrual Hygiene among Female Prisoners of Jhapa and Morang Districts of Nepal - Gautam, Laxmi; Regmi, Mamata; Bist, Amrit (Journal of Nepal Health Research Council, 2025)
Background: Female prisoners constitute a minority of prison population and their special health care needs are often neglected. This study aims to assess the knowledge of menstruation and menstrual hygiene practices of female prisoners of Jhapa and Morang.Methods: A cross sectional study was conducted among 140 female prisoners of Jhapa and Morang District Prison of Eastern Nepal through a pretested semi structured questionnaire and face to face interview. Logistic regression model was used to assess the factors associated with the outcome variable using an adjusted odds ratio with a 95% CI, and p-value <0.05 was considered statistically significant.Results: The study showed that 65% of the female prisoners had adequate knowledge about menstruation. Half of the respondents (50%) had good menstrual hygiene practice. Majority of the respondents (67.9%) used sanitary pad and nearly one third (32.9%) used clothes as absorbent material during menstruation. Dysmenorrhea was the major health problem (31.9%) reported by prisoners. Respondent’s knowledge on menstruation was significantly associated with educational status (AOR: 6.775, 95% CI: 2.089-21.87), marital status (AOR: 3.375, 95% CI: 1.979- 11.63) and former residence (AOR: 5.014, 95% CI: 2.196-11.44) in multivariate analysis.Conclusions: More than one third of female prisoners had inadequate knowledge about menstruation and half menstrual hygiene practices were unsatisfactory. This demonstrates a need to design health education programme and foster advocacy to improve the knowledge and promote safe hygienic practice of female prisoners during menstruation.Keywords: Female prisoners; inmates; menstrual hygiene; menstruation; Nepal.